Sistem Informasi Perpustakaan Sekolah Berbasis Web (Studi Kasus: SMAIT ULIL ALBAB KEC. CIBITUNG) - Nurlia Ftriani (LPPM STMIK AL MUSLIM, 2022)
SMAIT ULIL ALBAB - BEKASI is an Integrated Islamic Senior High School located in Wanasari Cibitung. Currently the existing library is not well coordinated. There are no visitor records, there is no history of borrowed books either. Many books that were from government assistance or independent purchases from schools were lost because they were borrowed but were not clear. There are also no loan data records. This causes schools to not have historical records of both books, borrowing and visitors, resulting in schools not having accurate data on the number of books in the school library. This requires a serious handling of the problem of recording data on borrowing books in the library so that the risk of schools losing books is small in this school. This study uses the waterfall method to design a web-based library information system at SMAIT Ulil Albab using PHP and MySQL. With the development of this system, every visitor can be recorded and stored in a database to be reported as library visitor statistics. With this system, the process of recording borrowing books using borrowing books has been abandoned, borrowing and returning inputs are more effective and efficient using the application. With this system, reports on how many books were borrowed that should have been returned, the status of the books and the total number of books in the library can be more easily made and can be printed according to the printing period.